The association between physical performance and subjective wellbeing in Chinese older adults: A cross-sectional study - Xie, Haiyang; Lu, Shenghua (Frontiers in Public Health, 2022)
Purpose: This study aimed to investigate the association between physical performance and subjective well-being among Chinese older adults. Methods: Data on the Chinese population were gathered from the Study on Global Aging and Adult Health Survey (SAGE). This survey used a stratified multistage cluster sample design based on geographical location and economic status. Chinese older adults aged 65 years old or above from eight provinces (Guangdong, Hubei, Jilin, Shaanxi, Shandong, Shanghai, Yunnan, and Zhejiang) were included in this cross-sectional study. Physical performance was measured using relative handgrip strength and normal gait speed. Subjective well-being was measured using quality-of-life (QOL), happiness, and mood through interviews with participants. Logistic regressions were used to examine the associations between physical performance and each of the three well-being variables (QOL, happiness, and mood). Results: Data on 5,421 Chinese older adults (mean age: 72.93 ±5.89 years old, 47.1% male) were analyzed. In this sample, individuals with a higher level of relative handgrip strength (rHGS) had better mood compared to those with a lower level of rHGS (p<0.05), and persons with lower gait speed had poorer QOL, happiness, and mood compared to those with faster gait speed (p<0.05). Conclusion: Our findings suggested that a higher level of relative handgrip strength predicted better mood; lower gait speed predicted poor QOL, happiness, and mood in Chinese older adults.